Pelatihan Foto Produk Sebagai Upaya Meningkatkan Kompetensi Mahasiswa Komunikasi dan Penyiaran Islam - Ainun Fitri Mughiroh; Robi’ah Machtumah Malayati (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
The application of digital marketing in the business world requires diverse skills, one of which is the ability to process visual content, such as photography, to make published products more appealing. This need arises because, in the current era of digital technological advancement, people tend to engage in buying and selling activities through online platforms. Consumers are more likely to be attracted to a product if its visual content is presented in a creative and engaging manner. This mentoring program aims to enhance participant’s skills in transforming products into visual content with creative and unique value. The program employs direct mentoring and hands-on practice, following the delivery of foundational photography theory to the trainees. Participants are divided into six groups, each assigned different tasks and photo concepts. This approach encourages teamwork among students in the Islamic Communication and Broadcasting program. In photography, producing a compelling work requires thorough preparation and a well-thought-out concept to ensure a smooth process and satisfactory results. The outcome of this program demonstrates that students have comprehended the materials provided by the mentors. This is evidenced by active interactions among participants discussing concepts, composition, proper photography techniques, lighting application, shooting angles, and other related aspects.